Tattoos on 18-year-old male adolescents - Characteristics and associated factors - José Froner Bicca; Rodrigo Pereira Duquia; Juliano de Avelar Breunig; Paulo Ricardo Martins de Souza; Hiram Larangeira de Almeida Jr (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Prevalence of tattoos is around 10-26% in men and 10-22% in women, and can involve negative effects such as: regret, removal attempts, physical and biological changes of the skin and association with some viral diseases. OBJECTIVE: to determine the prevalence, characteristics and factors associated with tattoos in recruiters joining the military. METHODS: the recruiters were examined by dermatologists that documented the presence or absence of tattoos, as well as their sizes, colors, designs and patterns, and whether they needed a parent's consent to get a tattoo. RESULTS: 1,968 recruiters were examined and the prevalence of tattoos was 10.82% (213), 141 (66.20%) had a single tattoo, 44 (20.66%) two tattoos, 15 (7.04%) three tattoos, 9 (4.23%) four tattoos, and 4 (1.88%) had more than four. Of the total sample, 168 (80.77%) reported getting the first tattoo before the age of 18. 158 (74.53%) were monochromatic. In relation to size, 108 (50.70%) had tattoos of up to 10 cm, 75 (35.21%) had tattoos measuring between 11-20cm, while 30 had ones over 21cm (14.09%). CONCLUSIONS: The population studied had a high prevalence of tattoos for their age, the percentage of complex (large and polychromatic) tattoos was also high.